Diversity and Inclusion of Human Resources: A Path to University Reputation through Faculty Engagement - M. Taamneh, Mohammad; Hija, Ayman Abu; M. Taamneh, Abdallah; makhamreh, Hiba (Journal of Ecohumanism, 2024)
The article intends to examine how diversity and inclusion affect the reputation of Jordanian universities and to explore if employee engagement acts as a mediator variable. Data was gathered from a sample of 509 faculty members in managerial academic roles (i.e deans, vice/assistant deans, department heads, and HRM unit administrative staff) in public and private universities in northern and central regions of Jordan using a questionnaire. This study is based on the premise that diversity and inclusion practices enhance universities' reputation. This study examines how employee engagement may act as a mediator variable. The study hypotheses were subsequently examined using Partial Least Squares Structural Equation Modeling (PLS SEM). The results indicated that diversity and inclusivity had a beneficial and noteworthy effect on universities' reputation. Diversity and inclusion were discovered to have a beneficial effect on employee engagement. Furthermore, the findings showed that employee engagement plays a partially mediating role in the connection between diversity, inclusion, and universities' reputation. This study's results expand existing research by presenting evidence from a non-western country like Jordan. The study discusses the theoretical and practical implications of the findings, along with limitations and recommendations for future research.